Knowledge, attitude, and practice toward sleep hygiene and cardiovascular health: a cross-sectional survey among healthcare workers - Sun, Weixin; Pan, Renyou; Song, Xiaolong; Gu, Tingting; Ni, Qimeng; Gu, Yuexing (Frontiers in Public Health, 2024)
Background Healthcare workers grapple with distinct challenges, inherent to their profession, making them susceptible to irregular sleep patterns and insufficient sleep, which may further impact their cardiovascular health. This study aimed to investigate the knowledge, attitude and practice (KAP) of healthcare workers concerning sleep hygiene and cardiovascular health. Methods A cross-sectional survey was conducted at Yancheng TCM Hospital Affiliated with Nanjing University of Chinese Medicine between July, 2023 and September, 2023. Demographic characteristics, KAP scores, sleep health awareness and habits, and sleep quality were assessed through the questionnaires. Results A total of 423 valid questionnaires were included in the study. Among these, 215 (50.83%) were aged 35 or below, and 128 (30.26%) reported suffering from chronic insomnia. The mean knowledge, attitude, and practice scores were 43.23 ± 5.67 (possible range: 10–50), 24.53 ± 4.59 (possible range: 9–45), and 20.22 ± 4.46 (possible range: 6–30), respectively. Multivariate analyses indicated that attitude score (OR = 0.890, 95% CI: [0.807–0.981], p = 0.019), sleep health awareness & habits score (OR = 1.847, 95% CI: [1.284–2.656], p = 0.001), experienced chest tightness or heart palpitations (OR = 6.084, 95% CI: [2.172–17.042], p = 0.001), and the presence of chronic insomnia (OR = 5.017, 95% CI: [2.428–10.368], p < 0.001) were independently associated with sleep quality. Conclusion Healthcare workers had adequate knowledge, negative attitude and moderate practice toward sleep hygiene and cardiovascular health. The findings highlight the need for targeted interventions to address the observed gaps in attitudes and practices, aiming to enhance overall awareness and promote healthier sleep habits among healthcare professionals.